Graffiti as a lever of critical awareness: a modern implementation of Freire’s pedagogical program - Mega, Georgia (Adult Education Critical Issues, 2022)
The content of the article deals with the the pedagogical approach of Paulo Freire in a fresh way. As is well known, the Brazilian Educator introduced for his time a pioneering approach to learning and teaching that awakens politically, stimulates socially and releases consciously, under conditions of dialogue. Through the sketches that Freire himself commissioned to important artists of his time, such as Francisco Brennand*, the adult learners gradually, not only became familiar with the use of basic vocabulary, reading and writing, but, moreover, through the process of coding and decoding they realized the source of their oppression and their potential human rights. Can the same thing happen today? Is it possible, public works of art to play an awakening role in the modern citizen’s consciousness and how? I elaborate this concern in the context of this article, taking into account the process of ‘codification’ and ‘decoding’ as traditionally defined by Freire (Freire 1974). The artistic trigger for the activation of the critical dialogue in the present socio-political context of humanity are contemporary works of art - such as graffiti. Graffities reflect a silent protest about what is happening that is accessible to all, since they are an integral part of the urban landscape of big cities around the world. From the wide range of graffities, the work of the artist STMTS* was selected for practical application of Freire’s principles. The artist’s works are well known not only in Greece, but also internationally. Their powerful metaphors challenge observers to reflect on the reality they experiencing in the modern world, under the guidance of Freire’s methodology.